Socioeconomic and Environmental Effects of Gold Mining in Paring Lahung, Montallat District, North Barito Regency - Karaskalo, Mario Fransisko Viegas; Zakiah, Wiwin; Pungan, Yudi; Yuniati, Ade (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2023)
This study aims to assess the impact of gold mining operations on the socioeconomic well-being of the Paring Lahung Village community in the Montallat District of North Barito Regency. The research utilizes both secondary and primary data sources. Secondary data is collected from many sources, such as the Central Bureau of Statistics (BPS), sub-district offices, villages/districts, and private entities. On the other hand, primary data is directly received from respondents residing in Paring Lahung Village, Montallat District, North Barito Regency. For a sample size of 30 participants. The research findings indicate that there is a discernible public impression regarding the presence of unauthorized gold mining operations in Paring Lahung Village. The findings indicate that the residents of Paring Lahung Village have a predominantly neutral stance towards gold mining operations. Out of the total number of respondents, 14 individuals (46%) expressed a positive attitude towards gold mining activities in the vicinity of the Paring Lahung Village forest area. Additionally, 9 respondents (30%) had a neutral view, while 7 respondents (24%) exhibited a negative attitude towards such activities. The present study examines the social, economic, and environmental conditions associated with the presence of gold mining activities in Paring Lahung Village. The analysis of social situations reveals that individuals distribute their wealth towards several sectors, including education, health, and housing. The economic conditions demonstrate a tendency towards above-average performance and have exhibited growth subsequent to the implementation of gold mining operations. This can be attributed to the augmentation of respondents' primary income, as well as the acquisition of supplementary sources of revenue. In Paring Lahung Village, the prevailing environmental conditions indicate the utilization of a method to separate combined gold and sand, alongside a minority engaging in conventional processing techniques. As per the accounts of certain inhabitants, the procedure of gold extraction involves the utilization of quicksilver, often known as mercury. Mercury is categorized as a heavy metal with the capacity to be designated as B3 trash